Scientometric Review of Cement-Less Ultra-High-Performance Concrete: Trends, Innovations, and Future Research Directions - Ali Ejaz; Anat Ruangrassamee; Muhammad J. Iqbal; Mitsuyasu Iwanami (Civil Engineering Journal, 2026)
This study presents a comprehensive scientometric review of cement-less ultra-high-performance concrete (UHPC) with the objective of identifying research trends, key contributors, dominant themes, and critical knowledge gaps in this emerging field. A systematic bibliometric analysis was conducted using the Scopus database, from which 59 peer-reviewed journal articles published between 2014 and 2024 were selected following rigorous screening criteria. Scientometric mapping was performed using VOSviewer to analyze publication trends, keyword co-occurrence, leading journals, influential authors, and active research regions. The findings reveal a sharp increase in research output after 2020, reflecting growing interest in geopolymer-based UHPC due to sustainability concerns. Existing studies predominantly focus on mechanical properties, particularly compressive strength and steel fiber reinforcement, while durability-related aspects such as corrosion resistance, fire performance, and long-term structural behavior remain underexplored. Higher sand-to-binder ratios (up to 0.8) were found to improve packing density and mechanical performance, achieving compressive strengths up to 160.7 MPa, while silica fume contents around 30% enhanced compressive strength by approximately 25% and fracture energy by nearly 50%. The novelty of this work lies in being the first dedicated scientometric assessment of cement-less UHPC, providing a quantitative overview of research evolution while systematically highlighting critical gaps and future research directions to support its effective structural application.